Studying Magnons in Iron Magnits with a Spin S= 1/2 According to the Heisnberg Triaxial Monoionic model in the Structured Coordinates - رستم زياد (Latakia University Journal -Basic Sciences Series, 2021)
This paper aims to studying magnons (a quasipartical of wave features) in the triaxial or monoionic magnetic iron environment according to the Heisnberg model, using an almost traditional way in the structured coordinates (Olar angles)starting from: 1- finding the suitable wav function of positive Hamiltone and Lagrangian, then the dynamic equations for calculating the energy levels. 2- finding Shrudinger equations for obtaining the energy levels. It was found that both ways give the same results. It was also found that this study (finding linear Shrudinger equations) can be applied in order to calculate the energy of free particles motion in magnetic iron crystals.